Active school commuting in adolescents from 28 countries across Africa, the Americas, and Asia: a temporal trends study - Mireia Felez-Nobrega; André O. Werneck; Adrian Bauman; Josep Maria Haro; Ai Koyanagi (BMC, 2023)
Abstract Background Evidence examining trends in active school commuting among adolescents are mainly single-country studies, and principally focused on high-income countries. Thus, the present study aims to examine temporal trends in adolescents' active school commuting and to examine if there are differences in such trends by sex. We used nationally representative samples of 28 countries, which were predominantly low- and middle-income countries (LMICs), covering 5 different WHO regions. Methods Data from the Global School-based Student Health Survey 2004-2017 were analyzed in 177,616 adolescents [mean (SD) age: 13.7 (1.0) years; 50.7% girls]. Active school commuting was self-reported (frequency of walking or riding a bike to and from school in the past 7 days). The prevalence and 95%CI of active school commuting (i.e., ≥ 3 days/week) was calculated for the overall sample and by sex for each survey. Crude linear trends in active school commuting were assessed by linear regression models. Interaction analyses were conducted to examine differing trends among boys and girls. Results Trends in active school commuting were heterogeneous across countries, with results showing stable patterns for the majority (16/28), decreasing trends for some (7/28) and increasing trends over time for a few (5/28). The majority of countries showed no differences in active school commuting trends between girls and boys. Conclusions The quantification of changes in adolescents' active school commuting over time, together with a deeper understanding of local determinants for such behaviors will provide valuable evidence to inform the development of tailored and context-specific actions.